Research on Language Teaching and Learning: Advances and Projection - Abad, José Vicente (Universidad Católica Luis Amigó, 2021)
In 2010, teachers from the B.A. in English Teaching at Universidad Católica Luis Amigó formed CILEX (Construcciones Investigativas en Lenguas Extranjeras). Research and teaching in the program have grown synergistically ever since, but ten years down the road it was time to take stock of our research to project the direction in which we wanted to move forward. This book is the result of that effort to recognize our shared history and thus propel our upcoming academic endeavors.